Family and Midwife Support in Perinatal Mental Health: A Mixed Methods Study - Pragastiwi, Enggar Avilia; Isnaeni, Yuli; Pratiwi, Cesa Septiana (Universitas Airlangga, 2026)
Background: Women's mental health during the perinatal period influences the well-being of mothers, infants, and families. Untreated perinatal depression can negatively affect health and quality of life for both mothers and babies. Objective: This study assesses the knowledge of midwives and experiences of perinatal women regarding mental health disorders, aiming to address gaps in comprehensive care during this period. Method: A mixed-methods design with a Sequential Explanatory approach was used. Quantitative data were collected from 103 women in the perinatal period and 23 midwives using the DASS-21 and Motherhope Indonesia questionnaires, analyzed via univariate methods. Qualitative data involved semi-structured interviews with five women and five midwives, selected through purposive sampling, analyzed phenomenologically. Results: Seventeen women reported anxiety symptoms, mainly due to new responsibilities and social pressures. Among midwives, 52.2% demonstrated good knowledge of perinatal mental health, 30.4% had adequate knowledge, and 17.4% showed deficiencies. Qualitative themes among women included symptoms, impacts, support received, and internal coping strategies. Midwives focused on their sources of knowledge, management techniques, and challenges in providing care. Women identified support systems, role understanding, and positive mindset cultivation as key in managing anxiety. Midwives emphasized the importance of formal and informal education, collaboration, and streamlined management procedures for effective detection and intervention. Conclusion: Family support plays a vital role in addressing mental health issues. Enhancing midwives’ roles in early detection and management through screening is essential to improve outcomes during the perinatal period.